Factitivity presupposition and the relativised predicate in Krio - Dudley K. Nylander (LibraryPress@UF, 1985)
After a brief review of the literature on factivity and presupposition, the paper examines a case of asymmetry in the interpretation of a construction known as the relativised predicate (RP). Whenever the main verb of the sentence with RP is mek (= 'make'), the sentence may be interpreted in two ways, including one with "the fact that". However, if the matrix verb is other than mek, there is only one interpretation possible-without "the fact that". It is concluded that the dual interpretation is possible because the relative particle (which is also a complementizer linked to factive verbs) associates with the factive mek.